2022
DOI: 10.1186/s12879-022-07040-y
|View full text |Cite
|
Sign up to set email alerts
|

A clinical prediction tool for extended-spectrum β-lactamase-producing Enterobacteriaceae urinary tract infection

Abstract: Background Prevalence of extended-spectrum beta-lactamase-producing-Enterobacteriaceae (ESBL-E) has risen in patients with urinary tract infections. The objective of this study was to determine explore the risk factors of ESBL-E infection in hospitalized patients and establish a predictive model. Methods This retrospective study included all patients with an Enterobacteriaceae-positive urine sample at the first affiliated hospital of Jinan universi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…Many previous studies have similarly documented being male as a predictor of ESBL urinary infection in adults ( Nakai et al, 2016 ; Lee et al, 2018 ). A recent retrospective study from China, which included a case series where 56% of the participants were over 60 years of age, showed that male gender, older age, hospital stay within the preceding 3 months, invasive urological procedure, and antibiotic use within the previous 3 months were independent factors associated with the development of an ESBL-positive Enterobacteriaceae UTI ( Liu et al, 2022 ). Similar risk factors, such as diabetes mellitus, recurrent UTIs, age over 60, and male gender, were also described by Rodríguez-Bano and Pascual (2004) .…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies have similarly documented being male as a predictor of ESBL urinary infection in adults ( Nakai et al, 2016 ; Lee et al, 2018 ). A recent retrospective study from China, which included a case series where 56% of the participants were over 60 years of age, showed that male gender, older age, hospital stay within the preceding 3 months, invasive urological procedure, and antibiotic use within the previous 3 months were independent factors associated with the development of an ESBL-positive Enterobacteriaceae UTI ( Liu et al, 2022 ). Similar risk factors, such as diabetes mellitus, recurrent UTIs, age over 60, and male gender, were also described by Rodríguez-Bano and Pascual (2004) .…”
Section: Discussionmentioning
confidence: 99%